Isolation of methyl caffeate and flacourtin from Flacourtia jangomas with comprehensive in-vitro and in-vivo pharmacological evaluation - Sadia Afreen Chowdhury; Rajib Das; Md. Ariful Haq; A.T.M. Zafrul Azam; Choudhury Mahmood Hasan; Monira Ahsan (Heliyon)
Background: Flacourtia jangomas, the Indian Coffee Plum or Indian Plum, is a medicinal plant found in Bangladesh and South Asia. Renowned for its potential as a source of bioactive compounds, this plant has garnered attention for its diverse therapeutic applications. This study aims to isolate phytochemicals and investigate the biological properties of methanol extracts from the bark of Flacourtia jangomas. Material and methods: The dried coarse plant powder was extracted with methanol and dried with a rotary evaporator. Then, the plant extract was subjected to phytochemical screening using various test reagents. Furthermore, extracts were investigated for isolating and characterizing chemical compounds and some of their biological activities. Results: The chloroform fraction of the methanolic extract of Flacourtia jangomas (MEFJ) yielded methyl caffeate and flacourtin, the first ever reported from this plant. Secondary metabolites were found via phytochemical screening, and total phenolic content was assessed. MEFJ was compared to BHT in the DPPH experiment for antioxidant potential. The brine shrimp lethality assay showed MEFJ's greater cytotoxicity than vincristine sulfate. Compared to streptokinase, increasing concentration increased thrombolytic activity and clot lysis. Compared to ciprofloxacin, F. jangomas did not exhibit substantial antibacterial activity (P < 0.001). The antifungal activity is not significant compared to Griseofulvin under the same conditions (P < 0.001). MEFJ stabilized membranes better than diclofenac sodium. The 400 mg/kg group inhibited acetic acid-induced analgesia by 70.32 %, but the control group did not. MEFJ at 200 mg/kg relieved pain better than the reference drug and 400 mg/kg in the hot plate test. This indicates the need for additional research. Conclusion: Flacourtia jangomas is a potential candidate for bioactive compounds, and further studies on the isolation and characterization of its bioactive compounds are highly required.